2012
DOI: 10.1038/cddis.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Twist1 sensitizes NSCLC cells to cisplatin via AMPK-activated mTOR inhibition

Abstract: Twist1 is highly expressed in primary and metastatic non-small cell lung cancer (NSCLC), and thus acts as a critical target for lung cancer chemotherapy. In the current study, we investigated the underlying mechanism initiated by silencing of Twist1 that sensitizes NSCLC cells to cisplatin. Silencing of Twist1 triggered ATP depletion, leading to AMP-activated protein kinase (AMPK)-activated mammalian target of rapamycin (mTOR) inhibition in NSCLC cells. AMPK-induced mTOR inhibition, in turn, resulted in downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…TWIST1 promotes resistance to apoptosis when cells are challenged with cisplatin in lung, bladder, and ovarian cancer, or paclitaxel in ovarian and prostate cancers . Here, we observed that COL11A1 interfered with cisplatin and paclitaxel‐induced apoptosis in ovarian cancer cells by upregulating NF‐κB/TWIST1‐mediated Mcl‐1 and GAS6 expression.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…TWIST1 promotes resistance to apoptosis when cells are challenged with cisplatin in lung, bladder, and ovarian cancer, or paclitaxel in ovarian and prostate cancers . Here, we observed that COL11A1 interfered with cisplatin and paclitaxel‐induced apoptosis in ovarian cancer cells by upregulating NF‐κB/TWIST1‐mediated Mcl‐1 and GAS6 expression.…”
Section: Discussionmentioning
confidence: 69%
“…Mcl‐1 has been shown to be a critical survival factor in ovarian cancer . Previous findings also indicated that TWIST1 knockdown enhances the sensitivity of cells to cisplatin through Mcl‐1 downregulation, which is linked to inhibited mTOR activity in lung cancer cells . GAS6 is known to inhibit apoptosis and GAS6 upregulation is a marker for poor prognosis in ovarian cancer .…”
Section: Discussionmentioning
confidence: 99%
“…While tumor cells with high levels of Twist presented F-actin filaments organized into actin stress fibers, silencing of Twist in 4T1 cells promoted cortical organization of F-actin in the areas of cell-to-cell contact. Although Twist was previously implicated in apoptotic evasion 43, in the 4T1 model, however, silencing Twist did not improve cells’ sensitivity to radiation or docetaxel treatment (data not shown). Altogether, our data indicate that Twist plays a functional role in the 4T1 model on the remodeling of the extracellular matrix as well as on the events of tumor cell migration and invasion.…”
Section: Resultsmentioning
confidence: 85%
“…(17) Several studies have established that the activation of Akt/mTOR signaling is strongly associated with advanced prostate tumors. (1820) Kremer et al (21) also reported a marked increased in the expression level of mTOR signaling pathway in prostate cancer tissues.…”
Section: Introductionmentioning
confidence: 99%